Phase I pharmacokinetic study of an oral, small-molecule MEK inhibitor tunlametinib in patients with advanced NRAS mutant melanoma - Zhao, Qian; Wang, Teng; Wang, Huanhuan; Cui, Cheng; Zhong, Wen; Fu, Diyi; Xi, Wanlin; Si, Lu; Guo, Jun; Cheng, Ying; Tian, Hongqi; Hu, Pei (Frontiers in Pharmacology, 2022)
Background: Malignant melanoma is an aggressive disease. Tunlametinib (HL-085) is a potent, selective, and orally bioavailable MEK1/2 inhibitor. The objective of this study was to determine the pharmacokinetics (PK) of tunlametinib and its main metabolite M8 in patients with NRAS-mutant melanoma following a single dose and multiple doses in a phase 1 safety and PK study. Methods: A multiple-center phase I study was performed in patients with melanoma including dose-escalation phase and dose-expansion phase. PK following a single oral dose and multiple doses of 0.5–18 mg twice daily was assessed. Results: A total of 30 participants were included in the dose escalation phase and then 11 patients were included in the dose-expansion phase (12 mg twice daily). Tunlametinib plasma concentration rapidly increased after dosing, with a Tmax of 0.5–1 h. Mean elimination half-life (t1/2) was dose- independent and had a range from 21.84 to 34.41 h. Mean apparent clearance (CL/F) and distribution volume (V/F) were 28.44–51.93 L/h and 1199.36-2009.26 L, respectively. The average accumulation ratios of AUC and Cmax after the multiple administration of tunlametinib were 1.64-2.73 and 0.82-2.49, respectively. Tunlametinib was rapidly transformed into the main metabolite M8, and M8 reached the peak concentration about 1 hour after administration. Mean t1/2 of M8 was 6.1-33.54 h. The body exposure of M8 in plasma was 36% to 67% of that of tunlametinib. There were general dose-proportional increases in maximum concentration (Cmax) and area under the curve (AUC) of tunlametinib and M8 both in the single dose phase and in the multiple doses phase. Conclusions: Tunlametinib was absorbed rapidly and eliminated at a medium speed after drug withdrawal. Pharmacokinetic body exposure increased in general dose-proportional manner from 0.5 mg up to 18 mg. Slight accumulation was found after multiple oral doses. The pharmacokinetics of tunlametinib and its metabolite suggest that twice daily dosing is appropriate for tunlametinib.